Looking back, reaching forward : a content analysis of asian journal of communication for the period 1990-1999 - Abraham, Ajit Varghese (2008)
This study was conducted with the general objective of finding out what kinds of research have been published in the Asian Journal of Communication (AJC) for the past nine years (1990 - 1999). The study addressed one broad research question - what trends could be seen in research articles published in the AJC? To answer this question, the principal researcher analyzed the research published in the AJC in terms of topic, Asian status, media focused on, countries covered, research design and methods used, number of authors, presence of a theoretical framework, and geographical origin of the references. The principal researcher also looked at the impact factor for the AJC, and trends in types of research published over its nine-year existence. The total population of 137 research articles published in the AJC was content analyzed. Descriptive statistics was used to analyse the data. The findings indicated that the journal has strong points that need to be developed. It also has aspects that could be changed so that the AJC might attract better contributions and garner a larger audience. Based on the findings, the study presented recommendations regarding the future direction of the AJC.